2015
DOI: 10.1007/s00784-015-1671-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of CaO-loaded electrospun matrices for bone tissue engineering

Abstract: Objectives To synthesize and characterize biodegradable polymer-based matrices loaded with CaO-nanoparticles for osteomyelitis treatment and bone tissue engineering. Materials and methods Poly(ε-caprolactone) (PCL) and PCL/gelatin (1:1, w/w) solutions containing CaO nanoparticles were electrospun into fibrous matrices. Scanning (SEM) and transmission (TEM) electron microscopy, Fourier Transformed Infrared (FTIR), Energy Dispersive X-ray Spectroscopy (EDS), contact angle (CA), tensile testing, and antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 51 publications
(58 reference statements)
0
25
0
Order By: Relevance
“…Previously displayed results stood that calcium-loading of polymeric membranes (less than 15 wt. % of CaO NPs, relative to the total polymer weight) was not harmful to cells [14]. In addition, zinc oxide NPs inclusion on same polymers (5, 15, and 30 wt % of ZnO NPs, relative to the polymer weight) increased membranes cell cytotoxicity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously displayed results stood that calcium-loading of polymeric membranes (less than 15 wt. % of CaO NPs, relative to the total polymer weight) was not harmful to cells [14]. In addition, zinc oxide NPs inclusion on same polymers (5, 15, and 30 wt % of ZnO NPs, relative to the polymer weight) increased membranes cell cytotoxicity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of ZnO NPs previously tested on human periodontal ligament fibroblast was found to strongly depend on concentration, being harmful at concentrations of 50 and 100 micrograms/mL [46]. It may be concluded that ionic zinc or calcium incorporation in the nanopolymer structure did exert lower cytotoxicity than when CaO or ZnO NPs are directly incorporated into the biomaterial [13,14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was explained that Ag/SiOC composite NFs are a promising material for antibacterial filtration application. Eventually, electrospun PCL/CaO NFs containing biodegradable and ceramic particles are used for tissue engineering [153]. Antibacterial activity results of the above-mentioned NFs show non activity, and MC3T3-E1 cell viability demonstrate the highest levels of activity for CaO-loaded matrices containing gelatin after 7 days in culture.…”
Section: Applications Of Ceramic Electrospun Matsmentioning
confidence: 99%
“…This is feasible by addition of inorganic nanoparticles into nanofibers, such as ceramic nanoparticles, for example hydroxyapatite [16,27,28,30], tricalcium phosphate [63,66], calcium oxide [67], or calcium silicate [24]; metal-based nanoparticles, for example gold nanoparticles [29], ferro- [62], or nanodiamonds [68]. These nanoparticles not only reinforce the polymeric nanofibers but also enhance their bioactivity in terms of increased cell adhesion, growth, osteogenic cell differentiation, bone matrix mineralization and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%